Present status and practical issues on dosimetry for the lens of the eye at JAEA MOX fuel facilities. Issue 1 (2nd January 2021) - Tsujimura, Norio; Yamazaki, Takumi; Takada, Chie
ABSTRACT: At Japan Atomic Energy Agency (JAEA) MOX fuel facilities, a worker usually wears a protective lead apron; therefore, the dose to the lens of the eye (lens dose) outside the apron is higher than that to the torso. To estimate the potential impact on the current facility operation of the International Commission of Radiological Protection (ICRP)-proposed lens dose limit reduction from 150 mSv/y to average 20 mSv/y, the authors carried out an analysis on the past dose records for the workers over the last 18 years. Of a total of 4, 312 workers' records analyzed, two workers' annual lens doses exceeded the lowered limit of 20 mSv (23.3 mSv and 20.7 mSv), although the maximum effective dose was below 10 mSv in each case. These compiled dose data reveal that in the glovebox and related operations the lens dose will be a limiting factor in radiological control under the newly lowered dose limit. To ensure that the number of workers with an annual lens dose greater than 15 mSv (approximately 0.6% of the workers) is kept to a minimum, the implementation of an administrative control level for the lens dose is considered.